KEWENANGAN DEWAN PERWAKILAN RAKYAT DALAM PEMILIHAN ANGGOTA BADAN PEMERIKSA KEUANGAN - Salsa Yaumil Akbari; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2022)
The prerequisites to join the Audit Board of the Republic of Indonesia (BPK) are governed by Law Number 15 of 2006 regulating the BPK Candidates must fulfill the following criteria in order to be elected as a member of the BPK: J. has been out of the state finance management environment for at least two years. What is the process for choosing members of the BPK for the years 2021 to 2026, and what are the legal repercussions if the procedures used by the House of Representatives to choose members of the Board do not adhere to the applicable laws? The research is normative legal in nature, uses secondary data as its primary source, is descriptive in nature, qualitatively examined, and draws findings deductively. The findings of the research, the discussion, and the conclusion show that there is a discrepancy between the process for choosing members of the Audit Board of the Republic of Indonesia in 2021 and the requirements set forth in Law Number 15 of 2006 concerning the BPK, also the legal repercussions that take place when the processes used to choose members of the BPK are in violation of applicable laws.